Implementation of the 2013 Scientific Curriculum Learning Strategy on Islamic Religious Subjects in State Elementary Schools III 101765 Bandar Setia - Arlina Arlina; Mutia Annisa; Nur Zannah; Zaidan Hamdani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to describe the implementation of scientific learning strategies in the 2013 Curriculum in Islamic Religious Education and its impact on the activeness of third-grade students at SD Negeri 101765 Bandar Setia. This research employed a qualitative approach with a phenomenological design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the application of scientific learning steps (5M), namely observing, questioning, collecting information, associating, and communicating, effectively enhances students’ activeness in asking questions, participating in discussions, and communicating learning outcomes. The learning process becomes more interactive, enjoyable, and meaningful. However, several challenges remain, including limited instructional time, differences in students’ literacy abilities, and less conducive classroom conditions. Therefore, more structured lesson planning and adaptive learning strategies are required to achieve optimal learning outcomes in Islamic Religious Education.